2023
DOI: 10.3390/healthcare11142057
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Physical Fitness and Risk of Hypertension in Korean Adults Aged 20–59

Abstract: Intervention for hypertension in young age groups is very important. Adults in their 30s and 40s in Korea are the main producers of economic activity. Stress in work life, frequent drinking and smoking, an unhealthy diet, and a lack of physical activity are the biggest factors that increase the risk of high blood pressure. This study analyzed obesity-related body composition, physical fitness, and risk according to age and sex by analyzing population-based hypertension and physical fitness trends in individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Our data also show relationship between blood pressure variability and renal progression. However, this again lost statistical significance in multivariate analysis, suggesting that the association is mediated through the confounding effect of other parameters such as advancing age, which is known to be associated with higher blood pressure variability [ 38 ]. Our data are consistent with the pooled analysis of the CANVAS and CREDENCE studies referred to above, which also found that SBP variability was not associated with kidney outcomes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data also show relationship between blood pressure variability and renal progression. However, this again lost statistical significance in multivariate analysis, suggesting that the association is mediated through the confounding effect of other parameters such as advancing age, which is known to be associated with higher blood pressure variability [ 38 ]. Our data are consistent with the pooled analysis of the CANVAS and CREDENCE studies referred to above, which also found that SBP variability was not associated with kidney outcomes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%